2001
DOI: 10.1073/pnas.241318498
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalized autocrine signaling to cystic fibrosis transmembrane conductance regulator at the apical membrane of airway epithelial cells

Abstract: Physical stimulation of airway surfaces evokes liquid secretion, but the events that mediate this vital protective function are not understood. When cystic fibrosis transmembrane conductance regulator (CFTR) channel activity was used as a functional readout, we found signaling elements compartmentalized at both extracellular and intracellular surfaces of the apical cell membrane that activate apical Cl ؊ conductance in Calu-3 cells. At the outer surface, ATP was released by physical stimuli, locally converted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
209
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 191 publications
(227 citation statements)
references
References 45 publications
(51 reference statements)
18
209
0
Order By: Relevance
“…Chloride flux measurements using MEQ indicated that A 2b receptor activation by adenosine increased apical chloride permeability by ∼2·5-fold over control. This increased chloride permeability is explained by the A 2b -adenylate cyclase-PKA-CFTR pathway (Huang et al, 2001). The role of A 2b receptors in ion transport is further confirmed by the use of general A 2 antagonist (DMPX) to inhibit A 2b activation by adenosine.…”
Section: Discussionmentioning
confidence: 81%
“…Chloride flux measurements using MEQ indicated that A 2b receptor activation by adenosine increased apical chloride permeability by ∼2·5-fold over control. This increased chloride permeability is explained by the A 2b -adenylate cyclase-PKA-CFTR pathway (Huang et al, 2001). The role of A 2b receptors in ion transport is further confirmed by the use of general A 2 antagonist (DMPX) to inhibit A 2b activation by adenosine.…”
Section: Discussionmentioning
confidence: 81%
“…39 and 40). In this model, regulation of CFTR is predicted to occur without any detectable changes in cytosolic second messenger concentration, because CFTR is intimately connected to signaling elicited by stimulation of A2B adenosine and ␤ 2 -adrenergic receptors (41)(42)(43). Moreover, type 2 lysophosphatidic acid receptors also form macromolecular complexes with CFTR that are mediated through a PDZ scaffolding protein (NHERF2).…”
Section: Discussionmentioning
confidence: 99%
“…While several G proteins localized to the apical membrane of the sweat duct cells, it was not clear which might be involved. In the apical membrane of airway epithelial cells G s couples activated adenosine A2b receptors to adenylate cyclase producing cAMP to stimulate PKA which phosphorylates and activates CFTR [33]. In the same cells, P2Y 2 purinergic receptors coupled to phospholipase C via G q may cause some activation of CFTR via a calcium-independent PKC activated by the diacyl glycerol released [50].…”
Section: Cftr Control By Phosphorylationmentioning
confidence: 99%